The Labor Market for New Ph.D. Economists: Panel Discussion - Auerbach, Alan J; Blau, Francine D; Shoven, John B (American Economic Review, 2004)
have provided us with a wealth of information about the newest products of U.S. Ph.D. programs. Among the notable facts are the continuing decline in the share of U.S. natives among these new graduates, their continued success at landing academic and other professional jobs, and their high level of professional fulfillment, in terms of both job satisfaction and outcomes measuring up to expectations. There are also a variety of intriguing results. For example, (from their table 5) students completing the top Ph.D. programs were younger, less likely to be married, and more likely to be foreign than those in the overall sample. Perhaps most disturbing, (from their table 6) median starting full-time academic salaries were lowest in public economics, a result that cannot be accounted for in salary regressions with other covariates. This clearly is an inversion of the appropriate ranking. In my comments, I will focus on two selected aspects of Ph.D. programs and the Ph.D. job market.